Selective bromochlorination of a homoallylic alcohol for the total synthesis of (−)-anverene - Seidl, Frederick J.; Burns, Noah Z. (Beilstein Journal of Organic Chemistry, 2016)
The scope of a recently reported method for the catalytic enantioselective bromochlorination of allylic alcohols is expanded to include a specific homoallylic alcohol. Critical factors for optimization of this reaction are highlighted. The utility of the product bromochloride is demonstrated by the first total synthesis of an antibacterial polyhalogenated monoterpene, (−)-anverene.
Keywords: enantioselective catalysis; halogenation; natural products; total synthesis